2009
DOI: 10.1111/j.1472-765x.2009.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of medium constituents for improved chitinase production byPaenibacillussp. D1 using statistical approach

Abstract: Aims:  Statistical optimization of medium components for improved chitinase production by Paenibacillus sp. D1. Methods and Results:  Urea, K2HPO4, chitin and yeast extract were identified as significant components influencing chitinase production by Paenibacillus sp. D1 using Plackett–Burman method. Response surface methodology (central composite design) was applied for further optimization. The concentrations of medium components for improved chitinase production were as follows (g l−1): urea, 0·33; K2HPO4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
2
28
1
Order By: Relevance
“…The unoptimized medium used for growth and protease production was as described earlier (Singh et al 2009) except that carbon (chitin) and nitrogen ((NH 4 ) 2 SO 4 ) source was replaced by protein source soybean meal, 10 g l -1 , pH 7.2. The organism was grown at 30°C under shaking conditions (180 rpm) for 72 h. The media components and their composition for protease production during optimization study are given in Tables 1 and 2.…”
Section: Organism and Culture Conditionsmentioning
confidence: 99%
“…The unoptimized medium used for growth and protease production was as described earlier (Singh et al 2009) except that carbon (chitin) and nitrogen ((NH 4 ) 2 SO 4 ) source was replaced by protein source soybean meal, 10 g l -1 , pH 7.2. The organism was grown at 30°C under shaking conditions (180 rpm) for 72 h. The media components and their composition for protease production during optimization study are given in Tables 1 and 2.…”
Section: Organism and Culture Conditionsmentioning
confidence: 99%
“…Yeast extract source had a significant effect on chitinase production. [26,33,34] Shrimp shell waste containing chitin source was reported to be an important factor for chitinase production. [35] Gohel et al [36] has reported CaCl 2 as an influential media constituent for chitinase production by Pantoea dispersa.…”
Section: Selection Of Important Medium Components Using Plackettàburmmentioning
confidence: 99%
“…[24] This design is useful in screening studies that uses only k C 1 treatment combinations to estimate the main effects of k factors independently, assuming that all interactions are insignificant. [23,25,26] A saturated design is used in the early stages of scientific tests in order to sort out unimportant factors from a large number of possible factors. When the number of factors in full factorial designs increases, the number of experiments becomes unmanageable.…”
Section: Introductionmentioning
confidence: 99%
“…4). The results for the reported chitinase production varied between 0.1 and more than 60 U/ml (Bhushan 2000;Vaidya et al 2001;Singh et al 2009;Souza et al 2009). These variations were observed because of the strains and the level of enzyme purification.…”
Section: Runsmentioning
confidence: 99%